2017
DOI: 10.1039/c7ra00360a
|View full text |Cite
|
Sign up to set email alerts
|

New amphiphilic polycarbonates with side functionalized cholesteryl groups as biomesogenic units: synthesis, structure and liquid crystal behavior

Abstract: In this study, a series of new side cholesterol-functionalized amphipathic copolymers based on an aliphatic polycarbonate backbone were synthesized and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…ROP of six-membered cyclic carbonates derived from glycerol was often performed in bulk using Sn­(Oct) 2 with heating over 100 °C. ,,,, In addition, the use of enzymes or some organic catalysts was reported. ,,, In most cases, ROP proceeded with a moderate control, and high-molecular-weight polymers were rarely obtained. To achieve the ROP of MDO in a controlled manner, different organobasic catalysts were employed as previously reported to mediate the controlled ROP for a variety of functional cyclic carbonates. , While for ROP of TMC, a binary catalyst system of DBU and an equimolar of the cocatalyst TU is required, , most of the substituted TMC monomers can be ring-opened by milder catalyst systems because the substituent often contributes to an increase in the polymerizability .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ROP of six-membered cyclic carbonates derived from glycerol was often performed in bulk using Sn­(Oct) 2 with heating over 100 °C. ,,,, In addition, the use of enzymes or some organic catalysts was reported. ,,, In most cases, ROP proceeded with a moderate control, and high-molecular-weight polymers were rarely obtained. To achieve the ROP of MDO in a controlled manner, different organobasic catalysts were employed as previously reported to mediate the controlled ROP for a variety of functional cyclic carbonates. , While for ROP of TMC, a binary catalyst system of DBU and an equimolar of the cocatalyst TU is required, , most of the substituted TMC monomers can be ring-opened by milder catalyst systems because the substituent often contributes to an increase in the polymerizability .…”
Section: Resultsmentioning
confidence: 99%
“…15,30 ROP of six-membered cyclic carbonates derived from glycerol was often performed in bulk using Sn(Oct) 2 with heating over 100 °C. 16,17,19,31,32 In addition, the use of enzymes or some organic catalysts was reported. 18,27,28,33 In most cases, ROP proceeded with a moderate control, and highmolecular-weight polymers were rarely obtained.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…POM showed that all the LC copolymers exhibited the fan-shaped texture of a smectic A (SmA) phase in heating and cooling processes. According to the results reported by Hu et al [ 29 ], the corresponding chiral monomer C showed a cholesteric phase. The result indicated that the macromolecular chain might hinder the formation of a cholesteric helical supermolecular structure and an ordered organization into the mesophase.…”
Section: Resultsmentioning
confidence: 73%
“…The synthetic route of the block copolymers is outlined in Scheme 1 . The cyclic monomer BTMC and the chiral LC monomer 6-cholesteroxy-6-oxocaproic acid (C) were synthesized according to our previous works [ 6 , 29 ].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation